Ketogenic diet in childhood epilepsy: clinical algorithm in a tertiary care center - Shaaban, Sanaa; Al-Beltagi, Mohammed; El Rashidy, Omnia; Nassar, May; El Gendy, Yasmin (Frontiers in Pediatrics, 2023)
Background Dietary therapies play a crucial role in managing patients, especially those who have specific types of epilepsy, display adverse effects, or are not responding to pharmacological treatments. The ketogenic diet (KD) is a high-fat, restricted carbohydrate, and adequate protein regimen. The KD has proven to be an effective nonpharmacological treatment for drug-resistant epilepsy (DRE) by generating ketones that act as an alternative fuel source for the brain, thereby reducing the occurrence of seizures. The advantages of KD have been attributed to its universal availability, numerous administration techniques, and affordability. Objective This article presents the KD algorithm developed by a multidisciplinary team of experts at the Children's Hospital, Ain Shams University, Egypt. The algorithm serves as a guide for implementing the KD in the treatment of DRE in children. The algorithm has been previously validated through a study. Methods The algorithm consists of seven essential stages: (1) referral of patients to the Complex Epilepsy Committee, (2) pre-diet assessment of patients, (3) referral of patients to the Clinical Nutrition (CN) team, (4) diet selection and initiation, (5) seizure follow-up and diet fine-tuning, (6) diet reassessment after 3 months, and (7) evaluation of the KD journey after 24 months. Results The KD algorithm was systematically developed and proved highly influential in facilitating the implementation of the KD. The algorithm yielded significant health benefits in pediatric patients. Conclusion The KD algorithm provides a systematic approach to implementing the ketogenic diet and has demonstrated positive health outcomes in pediatric patients.